Peran Online Travel Agent (Ota) dalam Mendukung Proses Reservasi Kamar di Discovery Kartika Plaza Hotel: Studi Kualitatif Dengan Analisis Tematik - Ni Komang Junita Mentarya Putri; I Putu Yoga Laksana; I Wayan Wirga (Universitas Kristen Indonesia Toraja, 2026)
The rapid advancement of digitalization has triggered a fundamental shift in the distribution system of the hospitality industry. This study aims to analyze the strategic contribution of Online Travel Agents (OTAs) in improving room reservation efficiency, identify supporting factors and operational technical constraints, and develop an ideal operational workflow. This study was motivated by the fluctuating occupancy rate at Discovery Kartika Plaza Hotel, which declined from 77.33% to 68.84%, accompanied by a decrease in OTA market performance from 51.22% to 48.94%. The research employed a descriptive qualitative method using Braun and Clarke’s thematic analysis approach. Primary data were collected through in-depth interviews with three key informants from the revenue management and e-commerce departments, complemented by field observations and document analysis. Data validity was ensured through source and method triangulation. The findings confirm that OTAs serve as a key pillar of the digital distribution ecosystem through automatic two-way integration with the Opera Property Management System (PMS) via the SiteMinder Channel Manager. Operational effectiveness is supported by stable technological infrastructure and optimized content quality scores. Conversely, data mapping synchronization delays (mapping lag) and limited system modification authority constitute the main technical constraints, potentially leading to overbooking. As a mitigation strategy, this study proposes a new operational workflow that incorporates proactive system monitoring to minimize data errors. The study concludes that digital platform automation requires consistent managerial oversight to sustainably optimize hotel revenue.